Miss Tacuarembó (Martin Sastre, 2010): Baroque thought to question the society that raised us - Rodríguez Riva, Lucía (2016)
Miss Tacuarembó, an Argentinian-Uruguayian co-production released in 2010, proposes a familiar story for Latin American audiences: a girl from a small town wants to success in the big city. Nevertheless, the baroque mise-en-scène of the film directly points to religious, family and show-business institutions through a camp sensibility, strengthening the ludic aspect of formats that are reworked and from which it is nourished, such as video and reality show. Thus, it builds a spectator that may identify him or herself with the main characters and simultaneously understand the operations and contradictions that constituted them as subjects, undoubtedly implying a political perspective on the notions of consume and popular culture.